2007
DOI: 10.1037/0894-4105.21.4.412
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal MRI and cognitive change in healthy elderly.

Abstract: Cross-sectional studies of normal aging indicate an association between memory and hippocampal volume, and between executive functioning and subcortical-frontal circuits. Much less is known, however, about the relationship between longitudinal MRI changes and cognitive decline. The authors hypothesized that longitudinal change in memory would be best predicted by change in hippocampal volumes, whereas change in executive functioning would be best predicted by cortical atrophy and progression of MRI markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
173
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(203 citation statements)
references
References 80 publications
21
173
2
7
Order By: Relevance
“…Our results for loss of healthy grey and white matter accord with those of a previous study by Kramer et al [2007]. They showed, in a sample of 50 adults assessed across a near‐identical period of life to the participants in the present study (from approximate mean age 74 years to 78 years, though with a wider range than our sample), that grey matter atrophy was associated with declining executive function (a composite measure that included one of the same tasks used here to index Fluid Intelligence, WAIS Digit Span Backward).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results for loss of healthy grey and white matter accord with those of a previous study by Kramer et al [2007]. They showed, in a sample of 50 adults assessed across a near‐identical period of life to the participants in the present study (from approximate mean age 74 years to 78 years, though with a wider range than our sample), that grey matter atrophy was associated with declining executive function (a composite measure that included one of the same tasks used here to index Fluid Intelligence, WAIS Digit Span Backward).…”
Section: Discussionsupporting
confidence: 93%
“…They showed, in a sample of 50 adults assessed across a near‐identical period of life to the participants in the present study (from approximate mean age 74 years to 78 years, though with a wider range than our sample), that grey matter atrophy was associated with declining executive function (a composite measure that included one of the same tasks used here to index Fluid Intelligence, WAIS Digit Span Backward). Also consistent with our results, Kramer et al [2007] found no link between total grey matter volume decline and reductions in memory, indexed by tasks similar to ours, including a list‐learning test.…”
Section: Discussionsupporting
confidence: 93%
“…This suggests that MetS induces brain changes comparable to accelerated aging. This is of clinical importance as the extent and rate of progression of global brain atrophy have been related to cognitive deterioration and conversion to dementia (28,29).…”
Section: Discussionmentioning
confidence: 99%
“…The question as to whether there is likely to exist a differential effect of total WMH burden on age-related morbidity based on the location within the CNS of white matter change remains unanswered. Longitudinal studies looking at the progression of WMH have been reported [9][10][11][12][13][14][15][16][17][18][19] ; however, differences in methodologies of WMH measurement make comparisons difficult. A poor cor-relation in estimated WMH burden between differing visual rating scales 20 and increased reliability and sensitivity of WMH volumetric measurements 21 make studies using volumetric measures preferable to those that use visual rating scales.…”
mentioning
confidence: 99%